Psychometric Evaluation and Comparison of Two Gaming Disorder Measures Derived From the DSM-5 and ICD-11 Frameworks - Wang, Hsin-Yi; Cheng, Cecilia (Frontiers in Psychiatry, 2020)
Gaming disorder was listed as a condition for further study in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) in 2013, and measures of the disorder have mushroomed in the years since. The Gaming Disorder Test (GDT) was developed after gaming disorder was officially included in the 11th Revision of the International Classification of Diseases (ICD-11) in 2018. However, it remains unknown whether the GDT, which is based on the ICD-11 framework, is psychometrically similar to or different from the popular nine-item Internet Gaming Disorder Scale-Short Form (IGDS9-SF) based on the DSM-5 framework. To address this important but unexplored issue, the present study evaluated and compared the psychometric properties of the GDT and IGDS9-SF in a sample of 544 adult gamers (56.2% men; mean age = 28.8, SD = 8.55). The results revealed both measures to have good reliability, structural validity, and criterion validity, with the exception of one IGDS9-SF item with a low factor loading. Moreover, the IGDS9-SF exhibited scalar measurement invariance for gender and age but only partial metric invariance for employment status, whereas the GDT exhibited scalar measurement invariance for all three demographic characteristics. Finally, the GDT displayed incremental validity over the IGDS9-SF in explaining gaming time, but not social anxiety and depressive symptoms. This study thus contributes to the literature by comparing measures derived from distinct gaming disorder diagnostic frameworks empirically. Recommendations for the selection of gaming disorder measures by researchers and practitioners are discussed.